Implementation of Internet Protocol Network Architecture for Effective bandwidth Allocation in a Multiparty, Multimedia Conferencing (Journal of Science and Technology, 2016)
Advances in multimedia technologies and development of overlay networks foster the opportunity for creating new value-added services over the current Internet. In this paper, a new service network architecture that supports multiparty multimedia conferencing applications, characteristics of which include multi-channel, high bandwidth and low delay tolerance has been proposed. The new service network architecture is built on an array of service nodes called Multiparty Processing Centers (MPCs) which constitute a service overlay network, serving as the infrastructure for multiparty conferencing, and are responsible for conferencing setup, media delivery and the provision of Quality of Service. In this paper, the main focus is on the bandwidth allocation management over the proposed service network. The analysis will determine the bandwidth demand for virtual links among the MPCs. Multimedia traffic is modeled as M/G/∞ input processes and divided into several classes, with the constraint that the aggregate effective bandwidth is within the link capacity times a prescribed utilization threshold.